metaxl: A package of tools to handle metadata - Iglésias, G.; Guimarães, P.; Silva, M. (The Stata Journal: Promoting communications on statistics and Stata, 2025)
In this article, we introduce metaxl, a community-contributed package designed for managing metadata in datasets. The package enables users to extract metadata from files into structured Excel files, making it easier to share and manipulate metadata independently of the data. It also allows for applying metadata from Excel files back to datasets, ensuring consistency across data extractions or survey waves. Additionally, metaxl offers functionalities for checking, comparing, and harmonizing metadata files, making it a valuable resource for managing large and complex datasets, particularly in settings where data security and quality are important.